2018
DOI: 10.1252/jcej.17we183
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ion-Exchange Membranes for the Membrane Bunsen Reaction in Thermochemical Hydrogen Production by Iodine-Sulfur Process

Abstract: Thermochemical hydrogen production by the iodine-sulfur process decomposes water into hydrogen and oxygen by combining the chemical reactions of iodine (I) and sulfur (S). Two types of acids are produced through the Bunsen reaction (I 2 SO 2 H 2 O 2HI H 2 SO 4). To improve the performance of this reaction, ion-exchange membranes for the membrane Bunsen reaction should be developed. In the present study, a cation-exchange membrane was prepared using a radiation-graft polymerization method. It was found that a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[14][15][16][17][18] In recent years, several types of membranes have been developed for the iodine-sulfur cycle. 4,[19][20][21][22][23][24][25][26][27][28] Myagmarjav et al reported that a hexyltrimethoxysilane (HTMOS) derived silica membrane achieved H 2 permeance on the order of 10 À7 mol m À2 s À1 Pa À1 with H 2 /HI selectivity of more than 175. 4 In addition, their silica-based ceramic membrane reactor achieved HI conversion of 0.70 and H 2 extraction of 0.98 at 400 C. 27 However, it was also reported that silica membranes can't survive under humid environments at high temperatures, 29 and challenges remain for the use of silica membranes when using water in Bunsen reaction and H 2 SO 4 decomposition reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18] In recent years, several types of membranes have been developed for the iodine-sulfur cycle. 4,[19][20][21][22][23][24][25][26][27][28] Myagmarjav et al reported that a hexyltrimethoxysilane (HTMOS) derived silica membrane achieved H 2 permeance on the order of 10 À7 mol m À2 s À1 Pa À1 with H 2 /HI selectivity of more than 175. 4 In addition, their silica-based ceramic membrane reactor achieved HI conversion of 0.70 and H 2 extraction of 0.98 at 400 C. 27 However, it was also reported that silica membranes can't survive under humid environments at high temperatures, 29 and challenges remain for the use of silica membranes when using water in Bunsen reaction and H 2 SO 4 decomposition reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Nomura et al proposed a cation exchange membrane (CEM) constructed from polymerized divinylbenzene on Naon for Bunsen reaction. 19 HI and H 2 SO 4 were obtained separately from CEM-divided cells by feeding SO 2 , I 2 and H 2 O. He et al discovered two Pt/carbon catalyst coated membranes (CCMs) that showed a reduced charge transfer resistance for the Bunsen reaction at room temperature.…”
Section: Introductionmentioning
confidence: 99%